Die Offenbarung des Johannes - Kraft, Heinrich (Mohr Siebeck, 1974)
The 4th edition of the first volume of this work provides an update of the commentary on the preamble and articles 1 to 19 in case law and literature. The structure of the book has been retained and its content supplemented by more recent developments, such as the implications of Europeanisation and digitalisation as well as the Corona pandemic. As of the 4th edition, Frauke Brosius-Gersdorf has taken over the editorship of the commentary.
PublicationDate: 20220826
Keywords: Apokalypse -- Studienliteratur -- Kommentare -- Neues Testament